(untitled) (African Journal of Biomedical Research, 2022)
Wastes are often discharged into surface water systems like rivers with little or no consideration for their assimilative capacities. In this study, we have investigated the pattern of river recovery for the upper river Ogun at varied points using six sampling stations of 250m interval i.e., upstream (ups 1, ups 2), dp (discharge point) and downstream (dst 1, dst 2 and dst 3) for 6-months across seasons. Samples analyzed for metals (Cd, Mn, Pb, Zn, Cu, Fe and Cr), in surface water and sediment showed a concentration gradient from the discharge point to downstream stations. All metals in sediment except Zn and Mn showed clear temporal patterns with higher concentrations in either dry season or rainy season. Discriminant function analysis (DFA) delineated sampling stations into least-polluted, intermediate- polluted and highest metal-polluted respectively. The classification of dst 3 alongside ups 1 and ups 2 suggests significant recovery 750m downstream from the discharge point. In general, although the river has experienced degradation, recovery to a condition close to its pre-disturbance state was observed.